Kekerasan Gender pada Naskah Drama Rajam (Pelempar Batu Pertama) Karya Idham Nurcahyo: Kajian Feminisme - Ali, Ayu Hidayanti; Kadir, Herson; Sadapu, Nurain; Justevani, Sri; Dunggio, Sri Juliana Mul’afaida (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
Violence against women remains a serious issue in society, both in the domestic and public spheres, and is often represented in literary works, including drama scripts. This study analyzes the drama script